A novel two‐dimensional crest factor reduction method based on concurrent output capacity of power amplifiers. Issue 3 (23rd October 2020) - Tang, Ke; Huang, Hang; Yu, Cuiping; Wu, Yongle; Jin, Qiuyan; Gao, Jinchun; Liu, Yuanan
Abstract: A novel two‐dimensional crest factor reduction (2D‐CFR) is proposed to improve the dual‐band concurrent performance of power amplifiers (PAs). The concurrent performance of target PA can be improved significantly when the power for peak detection conforms to the concurrent characteristic. Peak detection and clipping operation are presented based on concurrent output capacity of PAs, which can be efficiently described by introducing two design parameters. Measured results show that the drain efficiency is improved from 34.2% to 36.6% with the proposed 2D‐CFR when compared with the conventional 2D‐CFR while maintaining similar error vector magnitude and ACPRs, which indicates a significant performance improvement.